Excellence in business - Bovee, Courtland L. (Pearson Prentice Hall, 2005)
KEY BENEFIT: With its real-life examples and cases, and its lively, conversational writing style, Bovee/Thill/Mescon brings concepts to life and prepares students for obtaining and pursuing satisfying business careers. KEY TOPICS: Bovee/Thill/Mescon weaves a four-part pedagogical tool through out each chapter. It starts with Orient, which outlines what is going to be covered in the chapter and then connects these topics with a “role-model” business professional. Next is Explore, which looks at the skills that their “role-model” used in order to be successful. Third is Confirm, which revisits what they have learned in the chapter. And, finally, Apply allows students to use the skills they have learned in the chapter. MARKET: For introductory level business students.